Language, meaning, awareness: aspects of interdependence - Beskova, Irina A. (Вестник Пермского университета. Философия. Психология. Социология, 2024)
The question of correlation between languages of science and art should be considered in the context of solving a more general problem of connection between language, meaning, and the cognitive status of the receptivity realization in the process of a human’s individuation. An analysis of the prerequisites for the linguistic competence formation at the stage being ontogenetically earlier than the stage of isolated cognitive agents’ functioning, reveals new aspects of the contiguity of expressive resources and the experience that determines them. Reconstruction of some methodologically significant points of perceptive prenatal development introduces into epistemological discourse some layers of meanings that are innovative in their structure, fundamentally different from the structure of the contents that the subject manipulates in the postnatal period. Based on a logical-and-methodological analysis of the non-dual format of the implementation of cognition, the paper substantiates the possibility of a special kind of perceptualcommunicative procedures (expansion of consciousness, leap of awareness, «coming into being as a consciousness») that are capable of generating fundamentally new meaning schemas than those that a person uses in his individuated being-in-the-world. The mode of awareness leap as a basis of the linguistic competence formation becomes distinguishable in the optics of logical-and-methodological analysis of the non-dual stage of the perception coming into being. Such peculiar resources are correlated with the state of the subject’s cognitive integrity, when dissociation into thought and feeling, knowledge and beauty is not just absent, but is impossible. This is a state of indivisible mix of impressions, manifesting itself as a prerequisite, condition, source of formation of simultaneously fused meanings. Modal affiliation of these is not determined since the phenomenon of modal attribution at the stage of formation and functioning of such contents is not actualized. The proposed perspective of a deeper interpretation of the origins of the emergence of figurative and symbolic means of representing experience allows us to transform the optics of perception of a person’s cognitive potential in the context of more basic conditioning resources.